Case Report: Nephrotic syndrome as the primary manifestation of Alport syndrome in a Chinese pediatric patient - Song, Yue; Li, Yifei; Lu, Liqun; Yang, Changqiang; Lu, Jing (Frontiers in Pediatrics, 2025)
BackgroundAlport syndrome (AS) is a genetically heterogeneous disorder resulting from variants in genes coding for the alpha-3/4/5 chains of Collagen IV, leading to defective basement membranes in the kidney, cochlea, and eye. The clinical manifestations of AS vary in patients. Cases of childhood AS caused by COL4A3 presenting primarily with nephrotic syndrome (NS) are rarely reported. Here, we report a pediatric case presenting initially with NS attributed to AS caused by COL4A3.Case presentationAn 11-year-old boy presented with hematuria and nephrotic range proteinuria. After excluding secondary causes, primary NS was considered. He was administered with prednisone (60 mg/day). The patient had not responded to treatment by the end of 4 weeks, so he was diagnosed with steroid-resistant NS. A renal biopsy showed granular and vacuolar degeneration of renal tubular epithelial cells, multifocal foam cell infiltration in the renal interstitium, and immunofluorescence indicated the absence of α3, α4, and α5 expression in the glomerular and tubular basement membrane, while Bowman's capsule expression was normal. Electron microscopy ultrastructural suggested variable basement membrane thickness, and partial tearing and web-like structures. Genetic testing revealed a heterozygous COL4A3 missense mutation c.3210 (exon 37)G>A(NM:000091). These findings are consistent with the diagnosis of AS. Prednisone was gradually tapered and enalapril maleate was initiated.ConclusionWe have described a pediatric case of AS featuring NS as its primary manifestation. It is important to consider AS to be a diagnosis or differential diagnosis in patients who have NS with hematuria or steroid resistance.